A very young patient with Tubercular Meningitis and its complications - Akhter, Rowshan Jahan; Yasmeen, BH Nazma (Northern International Medical College Journal, 2020)
A case report on a successful management of an eight months old boy with Tubercular Meningitis with Multiple Tuberculoma in Brain with Obstructive Hydrocephalus with Left sided Lower motor neuron type Facial Palsy with Right Sided Hemiparesis. Tuberculous meningitis (TBM) is Mycobacterium tuberculosis infection of the Brain Meninges.1,2 In TBM inflammation occur mainly in the base of the brain and when the inflammation affect the brain stem subarachnoid area, cranial nerve roots then symptoms may occur like space-occupying lesions.3,4 TBM is more common in children than in adults, especially children aged 0-5 years.5 In children central nervous system tuberculosis usually presents as tubercular meningitis, post-tubercular meningitis hydrocephalus, and rarely a space-occupying lesions known as tuberculomas.6 TBM accounts for 2–5% of all active cases of Mycobacterium tuberculosis.7 Pulmonary infection coexists in 25–83% of TBM.8-10 Predominately primary CNS infection is found in children and leptomeningeal infection presents as meningitis, cranial nerve (CN) palsies (most commonly CN 2, 3, 4, and 7), and communicating hydrocephalus.11 Northern International Medical College Journal Vol.10 (2) Jan 2019: 400-401